Efektivitas Metode Kolaboratif Learning dan Kooperatif dalam Pendidikan Kesehatan Berbasis Komunitas - Tita Hariyanti; Harsono Mardiwiyoto; Yayi Suryo Prabandari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: The role of the learning methods is changing from teacher centered learning to student centered learning (SCL). One of the SCL methods is collaborative and cooperative learning. The past twenty years have seen an increase in collaborative and cooperative learning based pedagogies in colleges, but not in community based health education. The aim of this study is to identify the efectivity of collaborative and cooperative learning in community based health educationMethod: This research used quasi experimental non-randomized control group post test design. Respondent of the research are 111 geriatric cadres of Kecamatan Kepanjen and 72 geriatric cadres of Kecamatan Singosari.Results: Data shows that cadre’s knowledge in first training, 30 and 90 days after first training increased in both groups (p<0,001). There is no relationship between individual characteristic (age, education, occupation, time to work as a cadre, training) and increase of knowledge (p>0,05).Conclusion: Collaborative and cooperative method can increase cadre’s knowledge of stroke effectively and maintain memory retention longer than conventional method.